Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/tp.0000000000003844
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Maturation of Subcutaneous Pouch Can Improve Pancreatic Islets Engraftment in Rat Model

Abstract: A.P. performed the majority of surgical experiments and participated in data analysis and writing of the article. A.V. processed all samples for histological analysis, performed immunohistological and immunofluorescence staining, and participated in writing of the article. E.F. participated in research design and performed some surgical experiments. L.K. participated in islet isolation, cultivation, and transplantation and participated in writing of the article. A.H. participated in Original Basic Science Back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This leads to improved nutrient delivery and less loss of islet cells due to hypoxia and necrosis. Furthermore, it supports the glycemic control of the grafted islets in the scaffold, as also shown with a similar approach by Patikova et al 34 A possible disadvantage is the need for 2 separate surgical procedures. However, these are simple procedures that might even be done under local anesthesia.…”
Section: Discussionsupporting
confidence: 78%
“…This leads to improved nutrient delivery and less loss of islet cells due to hypoxia and necrosis. Furthermore, it supports the glycemic control of the grafted islets in the scaffold, as also shown with a similar approach by Patikova et al 34 A possible disadvantage is the need for 2 separate surgical procedures. However, these are simple procedures that might even be done under local anesthesia.…”
Section: Discussionsupporting
confidence: 78%
“…Distribution in the vicryl mesh prevented islet aggregation and promoted vascular infiltration. Patikova et al created a vascularized SQ space by implanting a microporous polyamide scaffold combined with a Teflon bar insert [65]. Interestingly, they found that a 5-day healing period after removal of the Teflon bar on day 7 (day 7 + 5) increased vascular density, whereas Teflon removal on day 28 resulted in rapid vessel regression.…”
Section: Direct Vascularization Macroencapsulationmentioning
confidence: 99%
“…Implantation of nylon catheters or cylindrical stainless-steel mesh tubing in rodents helped to create vascularized pouches in 1 month, exploiting the foreign body response (FBR) without inducing scar formation in different tissues. After removal, syngeneic islets or human islets were easily implanted, showing the ability to reverse diabetes in the respective appropriate rodent models (84), while islets infused in the not-preconditioned pouch were not able to restore normoglycemia (85)(86)(87)(88)(89). Similarly, poly-D,L-lactide-co-εcaprolactone (PLCL)-based scaffolds were used to prevascularize the subcutaneous space after 1 month.…”
Section: Vascularization and Oxygenation Of Transplantation Sitementioning
confidence: 99%